Structure Optimization and Test of the Tapered Roller Bearing based on the Decrease of Friction Torque - Mo Yimin; Wang Junping; Chai Shufeng (Jixie chuandong)
With the target of reducing the friction torque of tapered roller bearing,the globally optimal solution of bearing inner structural parameters is obtained by using the genetic algorithm.The friction torque,gearbox transmission efficiency,and vehicle fuel consumption and sliding distance are tested before and after the bearings are optimized.The results show that,the bearing friction torque is reduced,the gearbox transmission efficiency is increased,and the vehicle fuel consumption is slightly decreased while the vehicle sliding distance is highly improved.